Experimental verification of a wireless sensing and control system for structural control using MR dampers. - Loh, Chin-Hsiung
The performance aspects of a wireless ?active? sensor, including the reliability of the wireless communication channel for real-time data delivery and its application to feedback structural control, are explored in this study. First, the control of magnetorheological (MR) dampers using wireless sensors is examined. Second, the application of the MR-damper to actively control a half-scale three-storey steel building excited at its base by shaking table is studied using a wireless control system assembled from wireless active sensors. With an MR damper installed on each floor (three dampers total), structural responses during seismic excitation are measured by the system's wireless active sensors and wirelessly communicated to each other; upon receipt of response data, the wireless sensor interfaced to each MR damper calculates a desired control action using an LQG controller implemented in the wireless sensor's computational core. In this system, the wireless active sensor is responsible for the reception of response data, determination of optimal control forces, and the issuing of command signals to the MR damper. Various control solutions are formulated in this study and embedded in the wireless control system including centralized and decentralized control algorithms.
Keywords: Wireless active sensor; LQG control algorithm; MR-damper.; Decentralized control